Forensic interviewers’ experiences of interviewing children of different ages - Magnusson, Mikaela (Psychology, crime & law, 2020)
Increased knowledge about practitioners’ experiences of conducting forensic child interviews may provide valuable insights into the perceived challenges they encounter when questioning children. This mixed-methods study examined Swedish practitioners’ views on different interviewing components (ground rules, rapport building, practice narratives, question types), props, strategies for adapting their methods for preschool-aged children, and perceptions of challenges interviewing children of differing ages. Eighty-eight specialized forensic child interviewers responded to a national survey. The data was analyzed using quantitative and qualitative approaches. Attitudes regarding different interviewing components were mainly in line with current research recommendations. Prop use was primarily limited to drawings, photographs, and stress-reduction tools. A variety of strategies were used to adapt the existing protocol for questioning young children, indicating a potential need for additional standardized guidelines for this age group. Furthermore, the perceived barriers for children to disclose and the demands placed on the interviewer varied across age groups. Since all children should have the right to be questioned with age appropriate methods, we need to continue to develop ways of adapting practitioners’ interviewing strategies to match children’s developmental levels. To reach this aim, researchers may benefit from taking into account the concerns raised by forensic child interviewers.